Accounting for Business - Mohd Shariff, Ros Aniza (Entrepreneurship Development Centre (EDC, IIUM), 2020)
This chapter is about the introduction to apply the accounting technique in the business. Focusing on business, the chapter also draws attention to the accounting process.